STIMULI AND EFFECT OF THE INTENTION TO LEAVE THE ORGANIZATION - Halawi, Ali H. (European Scientific Journal, ESJ, 2014)
The intent to leave is a commonly studied phenomenon. In this paper, we have studied the intention to leave in two separate folds: Organization and Profession. The determinants and outcomes for these two aspects are identified from present literature. It is postulated that job satisfaction and organizational commitment has organic relationship with intention to leave organization and profession, and these two phenomena relate to intention to leave consistently through almost all determinants and outcomes. Therefore, it is suggested that by intentionally bringing satisfiers and commitment stimulators, organizations can benefit by controlling or eliminating such intentions totally, as they have dangerous effects on individual and organizational performance.